Protection measures for sustaining the identity of small towns in Malaysia / Nur Farhana Azmi - Nur Farhana, Azmi (2015)

(untitled)
Every town has beauty, unique and distinct characteristics of its own. Unfortunately, despite having rich historical and architectural reserves, towns of a small scale in South- East Asian countries including Malaysia have been overlooked. Thus, this research aimed to examine the protection measures with regard to sustaining the unique features and identity of small towns in Malaysia. This research seeks to identify place attachment indicators and characteristics of small towns in Malaysia based on case studies of Kuala Kubu Bharu in Selangor, Sungai Lembing in Pahang and Kampung Kepayang in Perak. The study also critically analyzes the existing plans, policies and legislation impacting development of small towns in Malaysia and recommends protection approaches to enhance and sustain the towns’ unique features and identity. The research adopts mixed methods approach as the appropriate research technique. Quantitatively, the study draws on questionnaire survey with residents and nonresidents of the towns. A total of 637 respondents were involved and different perceptions on elements and qualities associated with the towns’ identity were observed in the survey. The qualitative approach involves field observation and a series of semistructured interviews with nine key stakeholders from a range of organizations involved in heritage matters. The study also draws on a review of relevant international charters and guidelines as well as national, state and local approaches to built heritage protection. The findings highlight the physical built environment including both man-made and natural features, human activities as well as meanings and associations as the most fundamental components influencing the identity of small towns in Malaysia. However, this research reveals that the existing protection mechanisms have only limited impact on the locally significant places. Although there are provisions for protecting the places, iv the research concludes that the existing legislations, policies and plans are lacking and insufficient with regard to the protection of built heritage at the local level. Accordingly, the protection is solely based on discretion of the local authority and hence, creates faultiness about the place. In this regard, this research provides recommendations that take into consideration the existing character of a place for effective protection and enhancement of unique features and identity in small Malaysia towns. This approach requires greater cooperation between key stakeholders, financial assistance as well as the integration not only between tangible and intangible components of place identity but also integration of built heritage within the overall planning system.